2021
DOI: 10.2196/27886
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Return of Individual Patient-Reported Outcome Results Among Patients With Lymphoma: Randomized Controlled Trial

Abstract: Background There has been a cultural shift toward patient engagement in health, with a growing demand from patients to access their results. Objective The Lymphoma Intervention (LIVE) trial is conducted to examine the impact of return of individual patient-reported outcome (PRO) results and a web-based self-management intervention on psychological distress, self-management, satisfaction with information, and health care use in a population-based setting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…After completing ePROMs, patients and health care practitioners (HCPs) might receive (visualized) feedback. Feedback can be personalized comparing individual results with (1) their previous results; (2) with patients similar to them; or (3) with a normative population [ 15 , 16 , 17 ]. By being able to compare their own scores with a person of the same age and sex without cancer, a patient might be able to better interpret his/her own functioning.…”
Section: Epro Methodology and Implementationmentioning
confidence: 99%
“…After completing ePROMs, patients and health care practitioners (HCPs) might receive (visualized) feedback. Feedback can be personalized comparing individual results with (1) their previous results; (2) with patients similar to them; or (3) with a normative population [ 15 , 16 , 17 ]. By being able to compare their own scores with a person of the same age and sex without cancer, a patient might be able to better interpret his/her own functioning.…”
Section: Epro Methodology and Implementationmentioning
confidence: 99%
“…In total, 14 reports were identified as potentially eligible and underwent a full text review. Of these, six [ 26 , 27 , 28 , 29 , 30 , 31 ] were excluded, mainly because the outcomes of interest in this review were not measured or because the types of intervention or study aims were not eligible for our study question ( Table S1 ). Overall, six studies [ 32 , 33 , 34 , 35 , 36 , 37 ] were included in our systematic review, to which two follow-up publications [ 38 , 39 ] were added for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that the majority of patients (84%) were willing to use the portal; however, they also observed that the completion of ePROs decreased over time, mainly because of the patient’s forgetfulness, and suggested ways to increase long-term participation rates ( 19 ). In another recent study, 227 lymphoma and chronic lymphocytic leukemia patients who completed web-based PRO questionnaires were randomized to care as usual (CAU), or to CAU plus return of PRO results (with or without a web-based self-management intervention) ( 20 ). No negative effects, for example in terms of psychological distress, were observed when individual PRO results were returned to patients, and authors concluded that this approach can be safely implemented in routine care practice ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, 227 lymphoma and chronic lymphocytic leukemia patients who completed web-based PRO questionnaires were randomized to care as usual (CAU), or to CAU plus return of PRO results (with or without a web-based self-management intervention) ( 20 ). No negative effects, for example in terms of psychological distress, were observed when individual PRO results were returned to patients, and authors concluded that this approach can be safely implemented in routine care practice ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation